FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ORANG PRIBADI TERHADAP ETIKA PENGGELAPAN PAJAK (Studi Empiris pada Wajib Pajak Terdaftar di KPP Pratama Jayapura) - Helweldery, Bryando; Allolayuk, Theo; Matani, Cornelia D. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This research aims to determine the influence of taxation, tax-service, and taxation sanctions on taxÂ evasion. The population in this research is a registered taxpayer at KPP Pratama Jayapura. SamplingÂ is done according to the proportions, so that the number of respondents are fulfilled by a certainÂ characteristic of 100 respondents. The data analysis methods used in this study are validity, reliability,Â classical assumption test, hypothesized test and multiple linear regression. The results showed thatÂ partially understanding taxation positively affect tax evasion, while the tax authorities have no positiveÂ effect and the taxation sanctions have no positive effect on tax evasion In addition, the research has noÂ simultaneous effect on tax evasion at KPP Pratama Jayapura. The implications of this study show thatÂ tax evasion is seen as unethical action to do. The Directorate General of Taxation needs to socializeÂ the importance of taxation understanding to lower tax evasion rates.